(3GdfSH GdcHjQs - (3GHf GdSGFH GdcdHj , gTGe Hf eMeO CHj GdfUQ Hf GdSGFH Hf HTQ GdcdHj, CHh GdefPQ,J (B204 (3g` s ((3YeQ Hf SGde Hf eMeO Hf fLOg Hf eNOYI Hf YOi GHf feQ GHf hGba s)
(3ChdgG (B:s
(3hdO QHjYI Hf eYO Hf YOfGf s
(3BNQgG (B:s
(3BNQ cJGH eYO hGdjef GdcHjQ s
(3GfXQ Qbe (B199 (3JGQjNs
(3ai CfSGH YOfGf hbMWGfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B149s
Keywords: (3GdJGQjNs